The Impact of Transformational Leadership Styles on the Job Performance of Cycle Two School Teachers in Muscat Governorate, Sultanate of Oman: An Analytical Study - Al-Humaidi, Amal Saif (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the impact of transformational leadership styles among school principals on enhancing teachers' job performance, while also examining the mediating role of job satisfaction, intrinsic motivation, and professional flexibility. The research was conducted in Cycle two schools in the Governorate of Muscat, Sultanate of Oman. The study was grounded in a theoretical framework based on transformational leadership concepts, which position this leadership style as an effective approach for motivating teachers, developing their professional competencies, and fostering an educational environment geared toward excellence. The study employed an analytical methodology. Data were collected through a structured questionnaire comprising three main dimensions and distributed to a sample of 210 teachers, selected through a stratified random sampling technique. The data were analyzed using SPSS statistical tools, The findings revealed that transformational leadership is practiced at a very high level from the perspective of teachers. Additionally, teachers demonstrated a high degree of professional commitment and effective collaboration. The results further indicated that the mediating variables—particularly job satisfaction and professional flexibility—play a significant role in strengthening the relationship between transformational leadership and job performance. This highlights the importance of transformational leadership behaviors in achieving institutional goals within the education sector. The study concluded with several recommendations, most notably the need to adopt transformational leadership as a formal administrative model, to enhance the leadership competencies of school principals, and to prioritize the psychological and organizational factors that influence teacher performance, in alignment with the aspirations of Oman Vision 2040 for high-quality education.
Keywords: transformational leadership; job satisfaction; career development; inspirational motivation